Temporal and Spatial Evolution Features of Precipitable Water in China during a Recent 65-Year Period (1951–2015) - Hao Wang; Jianxin He (Advances in Meteorology)
Water vapor in the atmosphere is not only an important greenhouse gas, but also an important factor that significantly affects the variations of global climate and water circulation. This study utilized the National Centers for Environmental Prediction (NCEP) and Climate Prediction Center Merged Analysis of Precipitation (CMAP) reanalysis data to probe the temporal and spatial distribution features of atmospheric precipitable water (PW) in China during a recent 65-year period (1951–2015), and the relationship between PW and actual precipitation was also studied. The temporal and spatial distribution characteristics of PW in China presented an overall decreasing spatial trend from the southeast to northwest direction. The spatial distribution pattern of the first eigenvector demonstrated that the PW in China shows nationwide variation features with a varying amount of PW across different regions. The year 1967 was further identified as an important transition period for the temporal and spatial distribution characteristics of the PW. We also found that the PW had inherent variability of around 30 years. Regarding the relationship with precipitation, PW was most closely correlated with precipitation in the northeastern region and the upper northwestern region in China. Different regions displayed different efficiencies for converting PW to precipitation. The conclusions are useful for understanding the long-term water vapor evolution and its potential effects on precipitation in China.